Enhanced Performance of a Single Chamber Microbial Fuel Cell Using NiWO4/Reduced Graphene Oxide Coated Carbon Cloth Anode - Geetanjali; Rani R.; Kumar S. (My University, 2025)
Microbial fuel cell (MFC) technology has potential to generate bioelectricity. However, the low power density problem is considerably associated with anode materials and its performance. In this study, modified anodes for single chamber MFC (SMFC) have been developed using NiWO4 impregnated on reduced graphene oxide (rGO) (NWG) composite. The analytical and morphological properties of rGO, NiWO4 particles and NWG composites have been characterized by FTIR, XRD, SEM and TEM. The electrochemical activity and capacitance of modified anode(s) are determined by cyclic voltammetry and galvanostatics charge-discharge, respectively. Modified NWG composite (2 mmol)-carbon cloth (CC) anode has highest capacitance value of 47.27 ± 0.18 F cm−2. The maximum power density obtained by modified NWG composite (2 mmol)-CC anode was observed to be 1128 ± 42 mW m−2 which was 6.57 times higher than the unmodified anode (171 ± 8 mW m−2). Electrochemical impedance spectra results indicate a substantial improvement in electron transfer between the microbes and the modified NWG composites-CC anodes. The decrease in the internal resistance of SMFC system is observed due to the improved electrochemical capacitance and synergistic effect between NiWO4 and rGO. In conclusion, modified NWG composites-CC anodes enhance the performance considerably and show excellent potential in electrode surface electrocatalyst modifier in MFCs. © 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim